2015
DOI: 10.15261/serdj.22.119
|View full text |Cite
|
Sign up to set email alerts
|

Extraction Behavior of Metal Ions Using D2EHPA in Cyclopentyl Methyl Ether

Abstract: Cyclopentyl methyl ether (CPME) has been developed as a commercially available ethereal solvent for application to various chemical processes. In the present study, the extraction of transition metal ions using di-(2-ethylhexyl) phosphoric acid (D2EHPA) in CPME and dodecane was studied in order to evaluate the potential of CPME as a diluent in the liquid-liquid extraction process. Transition metal ions were extracted by a proton exchange reaction using D2EHPA in CPME. The degree of extraction into CPME was red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…A sigmoid curve was obtained where %E was the lowest at pH eq 2.5 and it increased sharply from 3.0 to 4.0 before it achieved its maximum at 4.5 to 5.4. It was discovered that this finding was similar to those reported by Oshima et al [8] for Cu 2+ extraction with D2EHPA. By considering a dimeric form of D2EHPA in used cooking oil, the general equation for the Cu 2+ extraction can be expressed as [9]: (2) Where is D2EHPA in the dimeric form and is the number of D2EHPA molecules that take part in the reaction.…”
Section: Extraction Proceduressupporting
confidence: 91%
“…A sigmoid curve was obtained where %E was the lowest at pH eq 2.5 and it increased sharply from 3.0 to 4.0 before it achieved its maximum at 4.5 to 5.4. It was discovered that this finding was similar to those reported by Oshima et al [8] for Cu 2+ extraction with D2EHPA. By considering a dimeric form of D2EHPA in used cooking oil, the general equation for the Cu 2+ extraction can be expressed as [9]: (2) Where is D2EHPA in the dimeric form and is the number of D2EHPA molecules that take part in the reaction.…”
Section: Extraction Proceduressupporting
confidence: 91%
“…Oshima et al [69] reported the extraction of transition metal ions by using di-2-(ethyl-2-hexyl)phosphoric acid (D2EHPA, one of the most frequently used acidic extractants )d iluted in CPME. Oshima et al [69] reported the extraction of transition metal ions by using di-2-(ethyl-2-hexyl)phosphoric acid (D2EHPA, one of the most frequently used acidic extractants )d iluted in CPME.…”
Section: Introduction:m Otivation For Eco-friendly Solvents and For Cpmementioning
confidence: 99%
“…Another research area in which CPME has been successfully used is the extraction of base metal ions. Oshima et al [69] reported the extraction of transition metal ions by using di-2-(ethyl-2-hexyl)phosphoric acid (D2EHPA, one of the most frequently used acidic extractants )d iluted in CPME. An extraction order in CPME (quantified by atomic absorption) of Fe III > Zn II > Cu II % Mn II % Ca II > Co II % Mg II % Ni II was comparable to a previously reported study that used kerosene.…”
Section: Introduction:m Otivation For Eco-friendly Solvents and For Cpmementioning
confidence: 99%
“…Therefore, the authors examined the potential of CPME as a solvent in liquid-liquid extraction processes for metal ions. Recently, extraction of transition metal ions such as Cu (II) and Ni(II) using di-(2-ethylhexyl) phosphoric acid (D2EHPA) in CPME has been studied [5]. The extraction equilibrium constant in CPME as the solvent is slightly reduced compared with that in dodecane.…”
Section: Introductionmentioning
confidence: 99%